2014
DOI: 10.1007/s00253-014-5820-6
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of acetate and ethanol on methane formation in biogas sludge

Abstract: Biochemical processes in biogas plants are still not fully understood. Especially, the identification of possible bottlenecks in the complex fermentation processes during biogas production might provide potential to increase the performance of biogas plants. To shed light on the question which group of organism constitutes the limiting factor in the anaerobic breakdown of organic material, biogas sludge from different mesophilic biogas plants was examined under various conditions. Therefore, biogas sludge was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The OM and NN seem to promote the growth of both methanogens and methanotrophs, as they were positively correlated with all abundances (Figure 4) and have positive effects on microbial abundance (Figure 5a). The positive correlation with OM can be easily understood, as the decomposition of OM provides energy and nutrients for microbial growth (Fontaine, Mariotti, & Abbadie, 2003;Refai, Wassmann, & Deppenmeier, 2014). It has been shown that the abundance of methanogens are significantly increased by OM addition (Asakawa, Akagawa-Matsushita, Koga, & Hayano, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The OM and NN seem to promote the growth of both methanogens and methanotrophs, as they were positively correlated with all abundances (Figure 4) and have positive effects on microbial abundance (Figure 5a). The positive correlation with OM can be easily understood, as the decomposition of OM provides energy and nutrients for microbial growth (Fontaine, Mariotti, & Abbadie, 2003;Refai, Wassmann, & Deppenmeier, 2014). It has been shown that the abundance of methanogens are significantly increased by OM addition (Asakawa, Akagawa-Matsushita, Koga, & Hayano, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Eight small-scale fed batch reactors used in the experiment were set up as previously described by Refai et al (2014a,b). Briefly, 200 g of biogas reactor material was transferred under anaerobic conditions to 1-L gas-tight glass bottles sealed with butyl rubber stoppers and locked with aluminum screw caps.…”
Section: Methodsmentioning
confidence: 99%
“…Due to low sampling material amounts, the replicated samples from the four individual reactors per treatment condition and sampling point were combined. Acetate and butyrate concentrations were determined by gas chromatography as previously described (Refai et al, 2014a).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were collected in sealed plastic bottles, transported under cooled conditions and stored in the laboratory at À80°C until nucleic acid extraction. Methane production of the biogas reactor samples was measured as previously described (Refai et al, 2014). Shortly, 20 g of biogas reactor material was transferred into 120 ml serum flasks under anaerobic conditions, sealed with a rubber stopper and purged with N2/CO2 (50/50%, 1 atm) for 10 min.…”
Section: Reactor Conditions and Samplingmentioning
confidence: 99%